Decline in childhood respiratory-related mortality after the introduction of the pneumococcal conjugate vaccine in Morocco - Nada Bennani Mechita; Majdouline Obtel; Abdelilah Elmarnissi; Laila Lahlou; Aziza Lyaghfouri; Imad Cherkaoui; Mustapha Mrabet; Rachid Razine; Redouane Abouqal (Elsevier, 2020)
Aim: The objective of this study was to analyse the effect of the introduction in 2010 of the pneumococcal conjugate vaccine (PCV) on the reduction in mortality from respiratory causes in children under 5 years in Morocco. Methods: Child mortality rates from respiratory cause were analysed using an interrupted time series analysis. Mortality rates from congenital and chromosomal causes were also analysed for comparative purposes. Results: In the post-vaccination period, child mortality rates from respiratory causes decreased by 28% (Mortality rate ratio (MRR) = 0.72, 95% CI: 0.58-0.83) and by 30% in children under 1 year (MRR = 0.70, 95% CI: 0.50-0.98). In children aged between 1 and 5 years, the decrease in the child mortality rate was not statistically significant (MRR = 0.99, 95% CI: 0.91-1.08). Mortality rates from congenital and chromosomal causes in the post-vaccination period were stable in children under 5 years (MRR = 1.19, 95% CI: 0.97-1.48), in children under 1 year (MRR = 1.15, 95% CI: 0.94-1.40) and in children aged between 1 and 5 years (MRR = 1.19, 95% CI: 0.97-1.48). Conclusion: The decrease in child mortality from respiratory causes in the post-vaccination period provides strong evidence of the effectiveness of PCV. Keywords: Child mortality, Pneumococcal conjugate vaccine, Interrupted time series analysis, Morocco